P070 Does exercise reduce fat free mass loss during very low energy diet-induced rapid weight loss? A systematic review and meta-analysis. (9th November 2022) - Lowrie, F; Phillips, C; Hogan, C; Tran, D; Marshall, N; Gordon, C; Yee, B; Cayanan, E
Abstract: A bi-directional relationship exists between obstructive sleep apnoea and obesity. Very low energy diets (VLEDs) have been show to significantly reduce weight in overweight and obese patients. However, they can cause excessive fat free mass (FFM) loss, which adversely impacts health. Concurrent exercise training is a potential method of mitigating FFM loss. This systematic review and meta-analysis aims to assess the impact of exercise on FFM loss during VLED-induced weight loss in the overweight and obese. Medline, Embase, Cochrane Register of Controlled Trials and CINAHL were searched from inception to December 2021 for studies that compared VLED groups with and without concurrent exercise in overweight and obese adults. Studies were included if they reported changes in FFM, VLED was restricted to less than 800kcal/day and exercise programmes were at least low intensity. Following duplicate removal, 6516 studies were screened and 63 full text articles were reviewed, of which 7 were included. The primary outcome is change in FFM between groups and a meta-analysis is planned if deemed appropriate. Results will be available in September. This review will provide evidence regarding the impact of exercise on FFM loss when undertaken concurrently with a VLED. Furthermore, it will help inform practice guidelines around exercise prescription for preserving FFM while undertaking a VLED to ensure better patient health outcomes. It will also help inform translational studies for weight reduction in overweight and obese sleep apnoeics.